Jocezia, a new Carpocorini genus from the Neotropics (Heteroptera: Pentatomidae: Pentatominae) - Dellapé, Gimena (2021)
Carpocorini is the largest tribe of Pentatominae, containing 127 genera and more than 500 species distributed worldwide.A new genus, Jocezia n. gen., and a new species, Jocezia inusitata n. sp., from Argentina are described and illustrated.The new genus is included in the Hypatropis group, together with the genera Hypatropis, Amauromelpia, Luridocimexand Stysiana, and characterized by the head in lateral view with the mandibular plates in a higher level than clypeus andthe absence of parameres. An updated key to the Hypatropis group genera is provided.